2020
DOI: 10.3847/1538-4357/ab660f
|View full text |Cite|
|
Sign up to set email alerts
|

Final Spitzer IRAC Observations of the Rise and Fall of SN 1987A

Abstract: Spitzer's final Infrared Array Camera (IRAC) observations of SN 1987A show the 3.6 and 4.5 µm emission from the equatorial ring (ER) continues a period of steady decline. Deconvolution of the images reveals that the emission is dominated by the ring, not the ejecta, and is brightest on the west side. Decomposition of the marginally resolved emission also confirms this, and shows that the west side of the ER has been brightening relative to the other portions of the ER. The infrared (IR) morphological changes r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
4
19
0
Order By: Relevance
“…The measurements at 31 µm are solely from SOFIA, while those at 10-12 µm and 19 µm were collected from different instruments with slightly different filter systems, so that they are not a completely uniform sample. Nevertheless, these light curves generally follow those estimated from Spitzer 3.6 and 4.5 µm measurements (Arendt et al 2020). Arendt et al (2020) demonstrated that the 3.6 and 4.5 µm light curves are well represented by a convolution of exponential decay and a Gaussian function.…”
Section: Light Curve Analysissupporting
confidence: 67%
See 2 more Smart Citations
“…The measurements at 31 µm are solely from SOFIA, while those at 10-12 µm and 19 µm were collected from different instruments with slightly different filter systems, so that they are not a completely uniform sample. Nevertheless, these light curves generally follow those estimated from Spitzer 3.6 and 4.5 µm measurements (Arendt et al 2020). Arendt et al (2020) demonstrated that the 3.6 and 4.5 µm light curves are well represented by a convolution of exponential decay and a Gaussian function.…”
Section: Light Curve Analysissupporting
confidence: 67%
“…Nevertheless, these light curves generally follow those estimated from Spitzer 3.6 and 4.5 µm measurements (Arendt et al 2020). Arendt et al (2020) demonstrated that the 3.6 and 4.5 µm light curves are well represented by a convolution of exponential decay and a Gaussian function. These fittings are extended to the 8 and 24 µm Spitzer bands, too.…”
Section: Light Curve Analysissupporting
confidence: 67%
See 1 more Smart Citation
“…Kotak et al 2009;Fabbri et al 2011;Meikle et al 2011;Szalai et al 2011;Szalai & Vinkó 2013), but also for e.g. SNe 1978K (Tanaka et al 2012), 1980K (Sugerman et al 2012), and for the famous SN 1987A (Bouchet et al 2006;Dwek et al 2010;Arendt et al 2016Arendt et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of the supernova (SN) remnant of SN 1987A (SNR 1987A) allows observations in recent years to better resolve the geometrical structure of the ejecta (e.g., Frank et al 2016;Larsson et al 2019;Miceli et al 2019;Arendt et al 2020), as well as to establish the properties of dust (e.g., Dwek & Arendt 2015;Matsuura et al 2019). These observations reveal a complicated non-spherical morphology of the ejecta.…”
Section: Introductionmentioning
confidence: 99%